TURNOVER INTENTION IN BANK EMPLOYEES: THE MEDIATING ROLE OF JOB SATISFACTION - Kirana, Nanda Wahyu Indah; Sunani, Avi; Widodo, Ulfa Puspa Wanti; Lukitasari, Ika Chandra; Permatasari, Lintang Putri (JURNAL DIMENSI, 2023)
The current study dealt with the work environment, job competence, and job satisfaction effect as potential determinants of the turnover intention of banking employees in Indonesia. Using the structural equation model, data were collected and analyzed from a final sample of 253 bank employees of Indonesian banking. The results show that the work environment in the baking industry and job competency play a critical role in preventing turnover intention. Moreover, job satisfaction plays an influential role in mediating the work environment in preventing turnover. Thus, stakeholders of the banking industries can improve the work environment and the level of employee competence to minimize the level of turnover intention. The implications of these findings are of practical significance for policymakers in the banking industry, as they provide insights on how to effectively reduce employee turnover rates inside their organizations.